Treated Coconut Coir Pith as Component of Cementitious Materials - Dana Koňáková; Eva Vejmelková; Monika Čáchová; Jamal Akhter Siddique; Kirill Polozhiy; Pavel Reiterman; Martin Keppert; Robert Černý (Advances in Materials Science and Engineering, 2015)
The presented paper deals with utilization of raw and treated coir pith as potential component of cementitious composites. The studied material is coir pith originating from a coconut production. Its applicability as cement mixture component was assessed in terms of the physical properties of concrete containing different amount of coir pith. Basic physical properties, compressive and bending strength, and hygric transport characteristics as well as thermal properties belong among the studied characteristics. It was proved that the concrete with 5% (by mass of cement) of this waste material shows appropriate physical properties and it gives rise to an applicable material for building structures. Generally, the coir pith can be regarded as lightening additive. When 10% of coir pith was added, it has led to higher deterioration of properties than what is acceptable since such dosing is greatly increasing the total porosity. The influence of chemical treatment of coir pith was evaluated as well; both tested treatment methods improved the performance of cementitious composites while the acetylation was somewhat more effective the treatment by NaOH.